2015
DOI: 10.1007/jhep10(2015)129
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative entanglement thermodynamics for AdS spacetime: renormalization

Abstract: Abstract:We study the effect of charged excitations in the AdS spacetime on the first law of entanglement thermodynamics. It is found that 'boosted' AdS black holes give rise to a more general form of first law which includes chemical potential and charge density. To obtain this result we have to resort to a second order perturbative calculation of entanglement entropy for small size subsystems. At first order the form of entanglement law remains unchanged even in the presence of charged excitations. But the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 18 publications
4
49
0
Order By: Relevance
“…However, V ∆P is an essential term in the first law when there is another variable in addition to r d + and a i in the metric. For example this is the case for the boosted black brane [27] and some other backgrounds. When we fix the size of the subsystem (l), the entanglement temperature and angular velocity can be obtained for d + 1 dimensional rotating cylindrical black holes to satisfy the entanglement first law (50).…”
Section: Holographic Entanglement Entropy Of D + 1 Dimensional Rotmentioning
confidence: 96%
“…However, V ∆P is an essential term in the first law when there is another variable in addition to r d + and a i in the metric. For example this is the case for the boosted black brane [27] and some other backgrounds. When we fix the size of the subsystem (l), the entanglement temperature and angular velocity can be obtained for d + 1 dimensional rotating cylindrical black holes to satisfy the entanglement first law (50).…”
Section: Holographic Entanglement Entropy Of D + 1 Dimensional Rotmentioning
confidence: 96%
“…These results are on expected lines. Quite importantly, the (KK) charge contribution in the first law is present at the first order itself, unlike in the relativistic cases studied in [7] where the contibution of the charges appears only at the second order. At the second order, once again we find that the first law relation requires the entanglement temperature (and strip width) to be suitably corrected or renormalised.…”
Section: Introductionmentioning
confidence: 91%
“…The boundary of such extremal surfaces coincides with the boundary of the subsystem in the CFT. Recently it has been observed that the excitations in the CFT follow entanglement laws similar to the black hole thermodynamic laws [5,6,7]; see also [9], [12], [10], [13]. It is understood now that the entanglement entropy (S E ) and the energy of small excitations (E) in AdS spacetime obey a definite relation…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations